THE EFFECT OF LEADERSHIP ON EMPLOOYEE PERFOMANCE: ANALYSIS OF THE MEDIATING AND MODERATING ROLE OF REWARD - Finna Fakhriyah; Yanuar Yanuar (International Journal of Application on Economics and Business, 2025)
Employee performance is an important factor in achieving organizational goals, with transformational leadership shown to improve performance through its influence on organizational commitment. However, a decline in productivity in Indonesian private companies and gaps in reward effectiveness prompted this study to develop a new research model. This Research aims to examine the impact of transformational leadership on employee work performance with organizational commitment as a mediating variable and reward as a moderating variable. This research was conducted on employees of PT X in Jakarta using quantitative methods by distributing questionnaires via googleform with 161 respondents and analyzed using Smartpls-SEM. The results showed that transformasional leadership offers a positive and significant effect on employee work performance. Organizational commitment is proven to mediate the relationship between transformational leadership and work performance, where employees who have high commitment tend to have better performance. However, extrinsic reward and perceived equitable reward did not moderate the relationship between transformasional leadership and work performance. Although rewards are important in creating satisfaction and motivation, employees at PT X are more influenced by intrinsic motivation and support provided by their leaders compared to extrinsic factors such as bonuses or other rewards. This research explores the important role of leadership and motivational strategies in improving employee performance. This research highlights the importance of fairness in rewarding employees, which ultimately provides valuable insights for company management to improve employee performance and motivation.